How many baby pandas? - Markle, Sandra (New York : Walker & Co., 2011)
Looks at the eight panda pairs that were born at China's Wolong Giant Panda Breeding and Research Center in 2005, examining how they live, grow, and play and the steps that are being taken to prepare them for their release into the wild.
Keywords: Giant panda; Counting